Perubahan Karakter Agronomi Aksesi Plasma Nutfah Kedelai di Lingkungan Ternaungi - Gatut Wahyu Anggoro Susanto; Titik Sundari (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2011)
Excessive shading during plant growth is one of the factors that might decrease the productivity of crops. The aim of this study was to determine agronomic characters of soybean germplasms grown under shaded environment. The research was carried out at Kendalpayak experimental station (grey Alluvial soil, 450 m above the sea level with C3 climate type) during dry season in Malang, from February to April 2006. The experimental design used was Randomized Complete Block Design with three replications. The genetic material observed were 120 accessions of Balitkabi’s soybean germplasm; the treatments were without shading and 50% shading using shading net. The results showed that 50% shading decreased plant age to harvest, increased plant height, and reduced the number of pods and seed weight compared to those in no shading environment. Based on Stress Tolerancy Index (STI) analysis on the seed weight per plant, fi ve accessions i.e. MLGG 0845, MLGG 3335, MLGG 0010, MLGG 0771, and Wilis demonstrated high tolerance on 50% shade